The aquatic processing of sclerophyllous and malacophyllous leaves on a Mediterranean island (Corsica) : spatial and temporal pattern (Annales de Limnologie - International Journal of Limnology, 1997)
Leaves of two species, alder (Alnus glutinosa) and holm-oak (Quercus ilex), were exposed in bags of two mesh sizes in two climatically contrasting sites of a Corsican softwater stream. Leaves were incubated both in winter and in summer for about 6 months. The field experiment was designed to determine the influence of both spatial (climate) and temporal (season) variations of temperature, as well as differences in the chemical and physical properties of sclerophyilous and malacophyllous leaves, on leaf decomposition rates. Comparisons were made between leaves colonized by macroinvertebrates and leaves protected by finemesh. In winter and summer, holm-oak leaves were colonized much less by macroinvertebrates than alder leaves. Spatial and temporal differences in leaf litter processing were mainly dependent on three factors (i) the chemical and physical properties of the leaves, (ii) the abundance of macroinvertebrates in the sediment and (iii) the temperature. The climatical pattern of temperature had a greater influence than its seasonal pattern. In contrast with many other studies, abiotic factors dominated over biotic factors in this study.